Essays on business cycles in emerging markets - Soave, Gian Paulo (2017)
The purpose of this thesis is to investigate the dynamics pertaining to emerging market business cycles, with special attention to the linkage between financial conditions and the behavior of the macroeconomic variables in such economies. Business cycles in emerging economies differ in many dimensions when compared with advanced economies: the former are characterized by much larger swings in real activity, financial markets, and policy driven variables. For example, when it comes to important macroeconomic variables, output tends to be twice as volatile in emerging economies compared to their developed counterparts. Another interesting discrepancy is related to the fiscal variables: while government consumption spending tends to be countercyclical in advanced economies, in many emerging economies, government spending is procyclical, which tends to reinforce the volatilities of the macro aggregates. The present work tries to shed some light on the role of financial instability in the emerging market business cycles and how the procyclicality of the fiscal policy can be attenuated by the introduction of fiscal debt-targeting rules. Chapter 1 starts by accessing the empirical implications of financial frictions for the business cycles and dynamics in emerging economies. Using a two-step procedure, the chapter first estimates unobservable financial stress indexes for 25 emerging markets to measure the evolution of the conditions of the financial markets in these countries over the period 1994Q1 to 2015Q4. With the financial indexes at hand, the chapter introduces a novel Hierarchical Bayesian Threshold VAR Model that uses Bayesian pooling to efficiently estimate the posteriors of the VAR parameters for each economy. The findings are summarized as follows: (a) stressful times occur with considerable frequency in the data (~ 30 % of the time); (b) second moments of the main macroeconomic variables are regime dependent, with consumption and investment being more correlated with GDP and with larger volatility for all variables considered under financial distress conditions; (c) consumption is more volatile that the GDP both in a regular financial condition and under a financial distress period; (d) the duration of the financial instability period is about 5.4 quarters; (e) nonlinear impulse responses show strong amplification effects related to the tightening of the credit conditions. In Chapter 2, a model in which financial instability emerges endogenously as an outcome of the presence of occasionally binding constraints is used to show that many of the nonlinearities documented in Chapter 1 can be understood as consequences of financial frictions. The chapter builds on a simplified version of the model introduced by Mendoza (2010) and features a Fisherian Debt-Deflation mechanism coupled with the presence of pecuniary externalities associated with the price of capital stock and wages. By using simulation techniques over fully nonlinear global solution methods, the channels through which financial friction affect the business cycles are disentangled. The Fisherian Debt-Deflation mechanism and the two pecuniary externalities magnify the volatility of the macro-variables whenever a crisis is expected in the future. In such a situation, uncertainty goes up and rational expectation agents increase precautionary savings to insure against the crisis. As extensions, two sources of financial frictions are added to the model: (i) a stochastic volatility in the process for the real interest rate - motivated by the results of the estimation of the time-varying parameters VAR (TVP-VAR) for 9 emerging economies; (ii) a financial shock affecting the collateral constraint. The results, conditioned on a specific regime, are consistent with those observed in Chapter 1. However, the additional sources of exogenous uncertainty pose a reduction in the likelihood of crises occurring because of the precautionary savings. This suggest that matching the observed frequency of regime switching is challenging for models with endogenous crises. Chapter 3 studies the implications of simple debt-dependent rules in emerging countries subject to endogenous financial crises with pecuniary externality. The analysis suggests that debt rules that account for the effects of debt accumulation on asset prices can be relatively more efficient in reducing the likelihood of financial crises, but can have substantial impacts on welfare whenever a crisis is likely to happen. Fiscal consolidations based on ad-hoc debt growth may be counterproductive during good times while having significant negative effects on welfare during crisis episodes. Simulated exercises suggest that, when carefully designed, fiscal rules based on debt target can result in welfare gains. Finally, it is worthwhile mentioning that, while solving the nonlinear models in Chapters 2 and 3, the thesis extends the algorithms developed in Maliar and Maliar (2013) and in Arellano et. al. (2016) of the so-called Envelop Condition Method to deal with occasionally binding constraints. This method, coupled with piece-wise linear interpolation/extrapolation techniques, is robust to the presence of the kinks in the policy function and capable of accounting for the distorted equilibrium and expectation effects.